Odpowiedź :
x-monety jednozłotowe
y-monety dwuzłotowe
x+y=27
y= x-3
x+x-3=27
y=x-3
2x=27+3
y=x-3
x=15
y=15-3
x=15
y=12
y-monety dwuzłotowe
x+y=27
y= x-3
x+x-3=27
y=x-3
2x=27+3
y=x-3
x=15
y=15-3
x=15
y=12
x monety jednozłotowe
y monety dwuzłotowe
x+2y=27
x=y+3
y+3+2y=27
3y=24/:3
y=8
x=8+3=11
spr.11razy1+8razy2=11+16=27
monet jednozłotowych jest 11 a dwuzłotowych 8.
y monety dwuzłotowe
x+2y=27
x=y+3
y+3+2y=27
3y=24/:3
y=8
x=8+3=11
spr.11razy1+8razy2=11+16=27
monet jednozłotowych jest 11 a dwuzłotowych 8.